Tinjauan Yuridis Terhadap Alasan Penerbitan Peraturan Pemerintah Pengganti Undang Undang Nomor 1 Tahun 2014 Tentang Pemilihan Kepala Daerah - Faisal Fahmi Siagian; Jamilah Jamilah (JUNCTO: Jurnal Ilmiah Hukum, 2020)
Government Regulation in Lieu of Law (Perpu) is one type of statutory regulation that must exist in the legal system of the Republic of Indonesia as one of the logical consequences of adopting a presidential system in the government of the Republic of Indonesia whose existence is always maintained throughout the Indonesian constitution. This type of research is normative juridical research and is descriptive qualitative in nature. Data collection methods are library research and field study. The affirmation of the benchmarks of the establishment of the Government Regulation in lieu of this Act has a fundamental difference regarding the urgency of the law according to the 1945 Constitution prior to the amendment to the 1945 Constitution which is currently in force as the result of the 4th amendment. After the reformation, there have been 2 (two) laws governing regional autonomy, especially with regard to regional head elections, namely Law Number 22 of 1999, which was then replaced by Law Number 32 of 2004. The issuance of Perpu Number 1 of 2014 which is a Amendments to Law No. 32/2004 were first proposed for amendments by the Government in this matter proposed by the Minister of the Interior.